Hur mår studenterna på Luleå tekniska universitet? : En kvantitativ studie om förekomsten av psykisk ohälsa bland universitetsstudenter - Johansson, Heidi; Mannberg, Sofia (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2019)
Mental illness among children and adolescents is increasing today. Many suffer from anxiety and depression, and a group that also experiences this is university students, which also confirms previous research (Socialstyrelsen, 2017; Folkhälsomyndigheten, 2018; Storrie et al., 2009). The purpose of this questionnaire study was to investigate the occurrence of mental illness at Luleå University of Technology through a quantitative method. The questions we formulated based on the purpose were whether students at Luleå University of Technology are experiencing mental illness, the underlying causes of the perceived mental illness, and whether there are significant differences between male and female students' perceived mental illness. The results of the study show that 82.4% of the respondents have experienced mental illness during their study period, and those students state that they have mainly experienced stress, anxiety and depression / depression. The underlying causes of mental illness are said to be stress, concern for the future and high demands. The result of our study showed no significant difference between women's and men's perceived mental illness, but it showed a tendency for women to experience mental ill health to a greater extent. Mental ill-health is widespread among university students, stigmatization is still great about the subject and many choose not to seek help. The result also indicates that the Student Health Service and the help they offer may need to be made more visible to reach out to the students. The analysis also shows that there is a connection between how one feels and what control one feels to have in life, poorer attitude showed lower control. Psykisk ohälsa bland barn och ungdomar ökar idag. Många lider av ångest och depressioner, och en grupp som också upplever detta är universitetsstudenter, vilket även tidigare forskning bekräftar (Socialstyrelsen,2017; Folkhälsomyndigheten, 2018; Storrie etal., 2009). Syftet med denna enkätstudie var att genom en kvantitativ metod ...